Increased Prevalence of Potentially Resistant Non-Aspergillus Molds Isolated in Lung Transplant Recipients after Voriconazole and Posaconazole Prophylaxis. (4th October 2017) - Fung, Monica; Greenland, John; Hays, Steven; Singer, Jonathan; Golden, Jeffrey; Chin-Hong, Peter
Abstract: Background: Lung transplant recipients are at higher risk for invasive fungal infections compared with recipients of other solid organs, potentially due to degree of immunosuppression, allograft exposure to the environment, and airway anatomical abnormalities. Because colonization with Aspergillus is a risk factor for chronic lung allograft dysfunction (CLAD), antifungal prophylaxis has become common. Few studies have examined the role of mold-active azole prophylaxis on the emergence of resistant fungal pathogens in this population. We hypothesized that voriconazole and posaconazole prophylaxis would be associated with increased rates of potentially resistant non- Aspergillus mold species such as Zygomycetes, Scedosporium, and Fusarium . Methods: We conducted a retrospective review of post-transplant bronchoalveolar lavage (BAL) culture results at our institution. We describe the non- Aspergillus mold species isolated and their prevalence over time. We used chi-squared tests to compare prevalence of non- Aspergillus molds before and after institution of voriconazole and posaconazole prophylaxis. Results: From August 2000 to February 2017, 557 subjects underwent BAL sampling, of whom 219 had 568 mold isolates cultured during 435 BAL events. Aspergillus species accounted for 61% of mold isolates; the most common non- Aspergillus species were Penicillium, Rhizopus, Sporotrichum, Scedosporium, and Fusarium (Figure 1). The prevalence of non- Aspergillus molds has increased over time (Figure 2). Prior to standard voriconazole prophylaxis in 2005, non- Aspergillus species were isolated in 0.9% of BAL specimens compared with 5.1% after ( P < 0.0001). Prior to incorporating posaconazole prophylaxis in 2014, the prevalence of non- Aspergillus molds in BAL specimens was 2.5% compared with 9.8% after ( P < 0.0001). Conclusion: The prevalence of non- Aspergillus molds in lung transplants recipients appears to be increasing in association with voriconazole and posaconazole prophylaxis. This shift in microbiology to more potentially resistant molds may make treatment of invasive fungal disease more challenging in this immunocompromised population. Additional study is also needed to better elucidate the role of non- Aspergillus molds in acute rejection and CLAD. Disclosures: All authors: No reported disclosures.